Research Progress of Traditional Chinese Medicine in the Treatment of Diabetic Retinopathy - Tang, Jiayu (Journal of Contemporary Medical Practice, 2025)
Diabetic retinopathy (DR) is one of the microvascular complications of diabetes. If it is not treated effectively in time, it will cause great damage and is a common blind eye disease. This article analyzes the understanding of traditional Chinese medicine of DR, summarizes the current situation of traditional Chinese medicine treatment of DR, and the research on the mechanism of traditional Chinese medicine treatment of DR. Clinically, traditional Chinese medicine adheres to the pathology, combines movement and static, and divides yin and yang, distinguishes viscera, and recognizes diseases with the overall concept. According to the main contradictions of patients, choosing the appropriate traditional Chinese medicine treatment has the advantages of improving clinical efficacy and reducing some complications of Western medicine treatment. However, there are still certain shortcomings and difficulties at present. For example, there is no consensus on the early pathological identification method of DR, the impact of the "metabolic memory" effect on the prevention and treatment of DR in diabetic patients has not been solved, and the diagnosis and treatment syndrome differentiation of DR has not been unified. This article has made a certain discussion and outlook on the above content, with a view to providing new ideas for clinical work.